2023
DOI: 10.3389/fimmu.2023.1184162
|View full text |Cite
|
Sign up to set email alerts
|

ITPKC polymorphism (rs7251246 T > C), coronary artery aneurysms, and thrombosis in patients with Kawasaki disease in a Southern Han Chinese population

Abstract: ObjectivesKawasaki disease (KD) is a commonly acquired pediatric systemic vasculitis disease resulting in coronary artery aneurysm (CAA). The relationship between the ITPKC polymorphism (rs7251246) and the severity and susceptibility to KD in the Han Chinese population in Southern China remains unclear.MethodsWe enrolled 262 children as controls and 221 children with KD (46 [20.8%] with intravenous immunoglobulin resistance and 82 [37.1%] with CAA). The relationship between the ITPKC rs7251246 polymorphism, KD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
1
1
Order By: Relevance
“…We used strict criteria for IVIG treatment in our study subjects in accordance with pharmacogenomics design. Accordingly, our results using different design and methodology did not replicate findings from prior studies such as associations with coronary aneurysms for variants in ITPKC 55 , KCNN2 54 , NEBL and TUBA3C 51 , SLC8A1 57 , and the matrix metalloproteinase ( MMP ) gene family 58 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We used strict criteria for IVIG treatment in our study subjects in accordance with pharmacogenomics design. Accordingly, our results using different design and methodology did not replicate findings from prior studies such as associations with coronary aneurysms for variants in ITPKC 55 , KCNN2 54 , NEBL and TUBA3C 51 , SLC8A1 57 , and the matrix metalloproteinase ( MMP ) gene family 58 .…”
Section: Discussioncontrasting
confidence: 99%
“…Prior studies, which have identified numerous significant variants associated with coronary aneurysms, did not account for the IVIG therapeutic effect. 53 54,55 Clinical trials clearly show that IVIG reduces the risk of CAA. 56 However, those previous genetic studies for the most part do not clarify whether study participants received appropriate IVIG treatment.…”
Section: Discussionmentioning
confidence: 99%